Organização e imprensa estudantil no Colégio de São Luiz e Liceu Maranhense: processo de formação de uma elite letrada (1949-1958) - Aquino, Mary Jones Ferreira de Moura (2016)
The present research investigates the different student organizations spawned between the years of 1949 and 1958 at the Colégio de São Luiz and the Liceu Maranhense. Both schools are located in the Brazilian city of São Luís, Maranhão state. At the Colégio de São Luiz, a private institution, there is the Grêmio Cultural e Recreativo "Luiz Rêgo", responsible for publishing the newspaper Avante (1949-50). At the Liceu Maranhense, a public institution, the students organized themselves in social fellowships or fraternities. Each had it's own newspaper: Folha Estudantil (1951), O Estudante de Atenas (1956-57), and O Liceu (1957-1958). Such organizations published literary texts on the school's everyday life and local and national political issues, as well as advertisements, circulating both in and outside the school. All such publications exist almost concomitantly to the emergence of a group of young writers in the late 1940s, prominent literary innovators and, in the following years, critics to the political and social life in Maranhão. This paper aims to problematize this group -- present in the collective memory of the city as the "Geração Maranhense de 45" --, in order to better understand the movement, and to better investigate the relationships with student organizations' newspapers. This paper also intends to understand the dynamics of sociability promoted by the student press among students, contributing to the understaing of their practices in the context of school culture of institutions. For the analysis of the newspapers, we used the referential methodology of Cruz and Peixoto (2007), and Luca (2011), and the investigation on sociability undertaken by Sirinelli's student press (1998)